Current and Emerging Topical Scar Mitigation Therapies for Craniofacial Burn Wound Healing - Kwon, Sun Hyung; Barrera, Janos A.; Noishiki, Chikage; Chen, Kellen; Henn, Dominic; Sheckter, Clifford C.; Gurtner, Geoffrey C. (Frontiers in Physiology, 2020)
Burn injury in the craniofacial region causes significant health and psychosocial consequences and presents unique reconstructive challenges. Healing of severely burned skin and underlying soft tissue is a dynamic process involving many pathophysiological factors, often leading to devastating outcomes such as the formation of hypertrophic scars and debilitating contractures. There are limited treatment options currently used for post-burn scar mitigation but recent advances in our knowledge of the cellular and molecular wound and scar pathophysiology have allowed for development of new treatment concepts. Clinical effectiveness of these experimental therapies is currently being evaluated. In this review, we discuss current topical therapies for craniofacial burn injuries and emerging new therapeutic concepts that are highly translational.